DETERMINAN PENGETAHUAN REMAJA TENTANG HIV/ AIDS DI KALIMANTAN SELATAN - Noorhayati Maslani; Serilaila Serilaila; Darmayanti Darmayanti; Nurlaili Habiba (Politeknik Kesehatan Kemenkes Bengkulu, 2022)
Problems: There is an increase in cases of HIV Aids in South Kalimantan every year, but different cases detected in the field are like an iceberg phenomenon. The incidence of this case is increasing in adolescents, while adolescents are the hope of the nation. One of the reasons is the lack of adolescent knowledge about HIV Aids which can affect behavior. The Aim Of The Research: The purpose of the study was to determine the determinants of adolescent knowledge about HIV Aids in South Kalimantan (2017 IDHS Data Analysis). Research Method: The research method is quantitative through a cross sectional approach using secondary data from the Indonesian Demographic and Health Survey (IDHS) in 2017. The population of adolescents aged 15-24 years in South Kalimantan is 585 respondents (total population). Data were analyzed by univariate and bivariate with chi square test. The Result: The results of the study were 55.7% of adolescents with good knowledge and there was a significant relationship with education level with p = 0.00 (OR = 1.864) and source of information with p = 0.00 (OR 2.198), while age, wealth quintile and place of residence were found there is no significant relationship to the knowledge of adolescents about HIV Aids in South Kalimantan. Conclusions: It is necessary to increase the knowledge of adolescents, especially about the mode of transmission and attitudes of people with HIV Aids through the use of information media or directly to teachers, peers and families by paying attention to the level of education of adolescents. Keywords: South Kalimantan, Adolescents, Knowledge of HIV/AIDS